Measurements of plasma zinc: Part I In health and disease. Issue 3 (May 1968) - Davies, I. J. T.; Musa, M.; Dormandy, T. L.
Abstract : Zinc is an essential trace element. Previous methods of measuring zinc in clinical material have been difficult and reported findings must be treated with caution. Using atomic absorption spectroscopy it has been established that plasma zinc is one of the most uniform biochemical characteristics of normal adult blood. Sex and age differences in adult life are insignificant. Increased metabolic activity, on the other hand, induces a marked, immediate fall in plasma zinc level. The possible implications of this are discussed. Zinc levels in patients with diabetes mellitus, cardiovascular disease, and anaemia due to acute blood loss have been within normal limits. Plasma zinc is low in certain types of liver disease.